Financial Analysis as Part of the Process of Determining the Value of the Company - Jana Kurotová; Miriam Jankalová; Veronika Kučmová (Communications of International Proceedings, 2020)
The present is characterized by the fact that companies are increasingly interested in finding out what is their value. In most cases, the issue is addressed by experts or expert organizations who, according to the individual steps of the prescribed process, try to determine the value of the company or its individual parts. The aim of this article is to perform a financial analysis of a selected company. Financial analysis is part of the process of determining the value of a company. The article performed a vertical and horizontal analysis, which forms part of the financial analysis. The input data used to achieve the results were drawn mainly from the financial statements of the selected company. The paper provides an overview of the financial situation of the selected company through analyses, whether vertical or horizontal, but also provides information on the financial health of the company through ratio indicators.
Keywords: Process; Financial Analysis; Value; Company.